2015
DOI: 10.1016/j.molcel.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Division Is Requisite to RAS-Induced Transformation and Targeted by Oncogenic MAPK Pathway Inhibitors

Abstract: SUMMARY Mitochondrial division is essential for mitosis and metazoan development, but a mechanistic role in cancer biology remains unknown. Here, we examine the direct effects of oncogenic RASG12V mediated cellular transformation on the mitochondrial dynamics machinery and observe a positive selection for dynamin related protein 1 (DRP1), a protein required for mitochondrial network division. Loss of DRP1 prevents RASG12V-induced mitochondrial dysfunction, and renders cells resistant to transformation. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
355
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(402 citation statements)
references
References 45 publications
24
355
1
7
Order By: Relevance
“…Recently, Ras-driven MEK-ERK signaling has been shown to activate Drp1-dependent mitochondrial fission (Serasinghe et al, 2015;Kashatus et al, 2015) in line with our previous finding that EGFR signaling (mediated by downstream activation of MEK-ERK signaling) promotes mitochondrial fission (Mitra et al, 2012). We have further shown that loss of Drp1-driven mitochondrial fission aberrantly enhances EGFR signaling to support aberrant cell proliferation (Mitra et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Recently, Ras-driven MEK-ERK signaling has been shown to activate Drp1-dependent mitochondrial fission (Serasinghe et al, 2015;Kashatus et al, 2015) in line with our previous finding that EGFR signaling (mediated by downstream activation of MEK-ERK signaling) promotes mitochondrial fission (Mitra et al, 2012). We have further shown that loss of Drp1-driven mitochondrial fission aberrantly enhances EGFR signaling to support aberrant cell proliferation (Mitra et al, 2012).…”
Section: Discussionsupporting
confidence: 84%
“…3C). Such boosted mitochondrial energetics in the absence of DRP1 has also been found in other mouse and human cells (Serasinghe et al, 2015;Kashatus et al, 2015). Furthermore, we found that the enhanced spare respiratory capacity between the DRP1-KO and WT MEFs was abrogated after 2 h of serum depletion, whereas both WT and DRP1-KO MEFs had enhanced spare respiratory capacity in the presence of serum (Fig.…”
Section: The Mtcyce Pool Is Modulated By Mitochondrial Bioenergetics supporting
confidence: 85%
See 1 more Smart Citation
“…49,60 In agreement with the previous observations, it has also been reported that several cancer cell lines or cells that have been transformed with oncogenes have more fragmented mitochondria than their non-transformed controls. 48,55,56,59 At least one of the molecular mechanisms involved in the maintenance of fragmented mitochondria in cancer cells has been recently elucidated and it has been proposed to involve the MAPK signaling pathway, a proliferation pathway activated in a variety of tumors. In normal cells, the RAS-RAF-MEK-ERK (MAPK) pathway is activated by growth factors and hormone signaling and its precise regulation controls proliferation and cell death.…”
Section: Mitochondrial Dynamics and Cancermentioning
confidence: 99%
“…Interestingly, the oncogenic MAPK/ERK pathway, which is a driver of cancer progression in different tumors, is able to upregulate Drp1 activity in different cancers [147,148] by phosphorylation on serine residue Ser616 [147]. In several human cancers, a poor survival rate is associated with an increased Drp1 level [54,67,70,71,144,149] or a decreased Mfn-2 [150,151] or Mfn-1 amounts [144,152], as also confirmed by the emerging Bioinformatics databases displaying the expression levels of different mitochondria-shaping proteins in human tumors (see The Human Atlas Project [153] and Table 1 for details).…”
Section: Mitochondrial Dynamics As Possible Therapeutic Targetsmentioning
confidence: 99%